Influence of HPV type on prognosis in patients diagnosed with invasive cervical cancer. Issue 11 (29th April 2014) - Cuschieri, K.; Brewster, D.H.; Graham, C.; Nicoll, S.; Williams, A.R.W.; Murray, G.I.; Millan, D.; Johannessen, I.; Hardie, A.; Cubie, H.A.
<x xml:space="preserve">Abstract</x> While much is known about the influence of HPV type on the progression of pre‐invasive cervical lesions, the impact of HPV type on cervical cancer prognosis is less evidenced. Thus, we assessed the impact of HPV type on the survival of women diagnosed with cervical cancer. A total of 370 cases of cervical cancer were assessed. Univariate analysis is presented using Kaplan–Meier survival curves and log‐rank statistics and multivariable Cox proportional hazard models were generated using age group, socio‐economic deprivation, FIGO stage, differentiation and HPV type. HPV grouping was considered in a number of ways with particular reference to the presence or absence of HPV 16 and/or 18. In the univariate analysis, FIGO, age at diagnosis and treatment were associated with poorer survival (p < 0.0001) as was absence of HPV 16 and/or 18 (p = 0.0460). The 25% mortality time in the non‐HPV 16/18 vs. HPV16/18 positive group was 615 days and 1, 307 days respectively. An unadjusted Cox PH model based HPV16/18 vs. no HPV 16/18 resulted in a hazard ratio of 0.669 (0.450, 0.995). Adjusting for deprivation, FIGO and age group resulted in a hazard ratio of 0.609 (0.395, 0.941) p = 0.025. These data indicate that cancers associated with HPV 16 and/or 18 do not confer worse survival compared to cancers associated with other types, and may indicate improved survival. Consequently, although HPV vaccine is likely to reduce the incidence of cervical cancer it may not indirectly improve cervical cancer survival by reducing the burden of those cancers caused by HPV16/18.